Feralisation targets different genomic loci to domestication in the chicken - M. Johnsson (Nature Portfolio, 2016)
Feralisation or the reintroduction of domestic animals into the wild population requires adaptation to survive. Here, the authors analyse the genetics of domestic chickens released into the wild and identify genomic regions that are selected for during feralisation.